Feminist Narratives in Memes through Socio-Cognitive Analysis - Perangin-angin, Alemina Br.; Ulfa, Maryam; Putri, Citra Anggia; Sujatmoko, Koko (TALENTA Publisher, 2025)
Using Van Dijk's socio-cognitive approach, this study examines ten feminist-themed memes from Pinterest, emphasizing the discursive, cognitive, and social elements. Three main themes emerge from the analysis of the memes: criticism of gender expectations, assertion of women's strength, and resistance to male control. The results show that women reject male control and dominance in memes under the first group (1.1; 1.3; 1.9), emphasizing female independence and resilience. The second category's memes (1.2, 1.4, 1.5, and 1.6) highlight women's strength and independence, demonstrating their capacity to subvert conventional wisdom and reinterpret social norms. The third category (1.7; 1.8; 1.10), on the other hand, criticizes what society expects of women and shows them as defying patriarchal stereotypes. This change demonstrates how digital discourse has developed into a platform that questions established hierarchies of power and encourages social criticism. These memes are vital resources for advancing feminist principles, empowering women, and raising awareness of gender equality because they use sarcasm and comedy. According to the study's findings, memes are more than just amusement; they are potent cultural artifacts that have the capacity to shape public opinion and promote constructive social change.